Programs of Local Government Sectoral to Improve the Welfare of Urban Communities - Akbar, Alexander; Faturohim, Agus; Hidayat, Bachtari Alam (Universitas Muhammadiyah Yogyakarta, 2023)
Poverty is a common problem faced by all regions in Indonesia, including Palembang City. Poverty is related to inequality and vulnerability because individuals who are not considered poor may at any time become poor if they experience economic shocks such as financial crises and inflation. Vulnerability is a key dimension of well-being because it can influence individual behavior in investing, production patterns, and the accuracy of the strategies implemented, as well as each individual's perception of how to respond to the situation at hand. This study examines the Poverty Reduction Strategy in Palembang City, South Sumatra Province. The purpose of this study is intended to reinforce the commitment of the Palembang City Government, non-governmental organizations, community organizations, business actors and concerned parties to solve the problem of poverty. Methods The poverty alleviation strategy in Palembang City is implemented through a participatory process which includes participatory poverty assessment (Poverty Assessment PPA), meetings, Regional Poverty Reduction Coordinating Team (TKPKD) Palembang City, joint studies with grassroots communities, and a series of coordinative meetings. The results of this study are that it is hoped that the regional government through the bureaucracy can formulate various policies and various sectoral programs in accordance with the tasks and fields of each of the Palembang City Regional Apparatuses. These sectoral programs are carried out with the aim of increasing the growth of each of these sectors, especially the lagging layers, namely the poor so that they can increase their ability to carry out activities as desired in an independent effort, able to fight for their rights, able to solve problems. faced and able to get equality of life with dignity in society.